PROJECT MANAGEMENT: A MANAGERIAL APPROACH - Mantel Jr Samuel J; Meredith Jack R (John Wiley & Sons, Ltd, 2006)
PROJECT MANAGEMENT IN OUR CONTEMPORARY SOCIETY IMPLEMENTING STRATEGY THROUGH PROJECTS MANAGING PROJECTS ORGANIZING PROJECTS THE PROCESS OF PLANNING PROJECTS
PROJECT MANAGEMENT IN OUR CONTEMPORARY SOCIETY IMPLEMENTING STRATEGY THROUGH PROJECTS MANAGING PROJECTS ORGANIZING PROJECTS THE PROCESS OF PLANNING PROJECTS